The Influence Of Operational Management On The Performance Of Battery Distribution Companies At PT. Abadi Sakti Mitra Mandiri - Ahmad Fadhilah Wibowo; Hepiana Patmarina (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
The purpose of this study was to find the effect of operational management on company performance. Operations management is the strategic management of resources to maximize the efficiency and effectiveness of the transformation process, resulting in outputs that produce greater benefits than inputs. Company performance is a level to get results in achieving company goals. The results of this work are concrete, observable, and measurable. The results of this work are concrete, observable, and measurable. This study uses quantitative methods with data processing and analysis to draw conclusions in the form of numeric data (numbers) which will obtain results from the relationship between variables. Multiple linear regression tests, reliability and validity tests, hypothesis testing (partial T test) and (simultaneous F test), and the coefficient of determination. In the research conducted, the sample used was 35 people in the company. The results of this study are linear regression analysis states that the Operational Management Variable has a positive and significant effect on Company Performance at PT Abadi Sakti Mitra Mandiri, with a regression coefficient of 0.968. That way the questionnaire as an instrument is declared feasible.